2019
DOI: 10.1080/03043797.2019.1677562
|View full text |Cite
|
Sign up to set email alerts
|

Exploring staff attitudes to distance learning – what are the opportunities, challenges and impacts on engineering academics and instructional designers

Abstract: Exploring staff attitudes to distance learning-what are the opportunities, challenges and impacts on engineering academics and instructional designers. Higher Education Institutions often see distance learning as a means of expanding student numbers and increasing global reach and reputation. Much of the academic literature, however, remains focused on the impact of distance learning on students and the technologies that support it, rather than considering the impact on those staff that are tasked with designi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The development of information technology is currently creating a distance learning process that supports students' needs for more optimal learning (Olapiriyakul & Scher, 2006). Meanwhile, for higher education providers, distance learning requires low costs, is flexible, and reaches a larger market (Casey, 2008), (Saunders et al, 2020). However, distance learning still has limitations, including control from students who are less independent, and many students cannot manage themselves and need direction from their lecturers (Rovai & Jordan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The development of information technology is currently creating a distance learning process that supports students' needs for more optimal learning (Olapiriyakul & Scher, 2006). Meanwhile, for higher education providers, distance learning requires low costs, is flexible, and reaches a larger market (Casey, 2008), (Saunders et al, 2020). However, distance learning still has limitations, including control from students who are less independent, and many students cannot manage themselves and need direction from their lecturers (Rovai & Jordan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The term "entrepreneurial ecosystem" has been used to describe the framework within which each entrepreneur interacts with other actors. Previous research has shown that the success of entrepreneurship depends on the actors who support it in its business [7]. Despite the linkage of the external environment with stakeholder support for sustainable entrepreneurship and the existing literature on "entrepreneurship in context" [8], there are only a few studies that examine the factors for achieving sustainable entrepreneurship [9].…”
Section: Introductionmentioning
confidence: 99%